Land policy in perspective - Subedi, Nab Raj (Journal on Geoinformatics, Nepal, 2009)
Fundamental entity where the existence resides is Land. Obviously being the basis of life and then source of wealth and power, land has been observed as a focal entity of social conflict and disorder. Any government willing to pay attention for good governance must give its eyes on the issues of land, otherwise, any effort made in the name of development will be like pouring water on sand. Being encapsulated by the strong but better political will for doing something to raise the people up from their plight and blight of abject poverty, it is urgently needed to formulate land policy whereby all policy implementation instruments will be systematically arranged within the skeleton of land policy framework. Land tenure security, land market, land valuation and taxation, land use planning and land reform are the main instruments envisaged in this paper ignoring which the expected gain out of the applied effort on any land issue can not meet the demand of the society. The block composed by these implementation instruments will rest on the system of land administration, acting as a tool designed to be matched with the land policy.